2019
DOI: 10.35940/ijrte.d8370.118419
|View full text |Cite
|
Sign up to set email alerts
|

Tourists Perception of Public Transit Services for Leisure Travel Satisfaction in Lagos

Abstract: This study determined to promote leisure satisfaction through pleasurable travel experiences in an active tourist destination. Local transportation provides links between tourists’ population and leisure targets at destinations. Therefore, diverse leisure activities and innovative tourism enterprises in many active cities are regulated by transport services. This study found that tourists are unwilling to adopt public mass transits for satisfactory travel in Lagos due to unattractive service attributes, thereb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
2
0
Order By: Relevance
“…The coefficient of determination is 0.778, which confirms that 77.8% of changes in the dependent variable can be explained through the independent variable (Mashoufi & Azami, 2019). In addition, a study in Lagos, Nigeria, found that tourists are unwilling to adopt public mass transit for satisfactory travel due to unattractive service attributes, thereby encouraging increased use of private vehicles for active leisure travel, which technically hampers the city's tourist appeal (Oluwatosin et al, 2019).…”
Section: Public Transportmentioning
confidence: 64%
“…The coefficient of determination is 0.778, which confirms that 77.8% of changes in the dependent variable can be explained through the independent variable (Mashoufi & Azami, 2019). In addition, a study in Lagos, Nigeria, found that tourists are unwilling to adopt public mass transit for satisfactory travel due to unattractive service attributes, thereby encouraging increased use of private vehicles for active leisure travel, which technically hampers the city's tourist appeal (Oluwatosin et al, 2019).…”
Section: Public Transportmentioning
confidence: 64%
“…In the case of Lagos State, Nigeria, a study by Oloruntobi et al [2019] found that inadequate transport infrastructure and poor service quality of public transport modes are a major challenge for tourism development in the Lagos region. The study indicates that poor road networks, insufficient public transport options, and limited accessibility to tourist sites have resulted in low tourism performance in Lagos State.…”
Section: Literature Reviewmentioning
confidence: 99%